Macroeconomics for budgeting and fiscal policy (Abuja : USIAD/Development alternatives inc., 2004)
This document is intended to provided a primer on a range of issues-concepts in macroeconomics to public expenditure management and budgeting. The paper further examines the theory and practice of budgeting and fiscal policy in relation to macroeconomics.
asm; 16/04/19
Loans
Keywords: Macroeconomics; Budgeting; Economic conditions; Macroeconomics; Nigeria